High rate failure properties of porcine aortic tissue under uniaxial tension. Issue 1 (2nd January 2021) - Gaur, Piyush; Sharma, Sanyam; Kumar, Devendra; Chawla, Anoop; Mukherjee, Sudipto; Lalwani, Sanjeev; Malhotra, Rajesh
Abstract: Traumatic aortic rupture (TAR) is believed to be the second most common cause of fatality associated with motor vehicle crashes(MVCs) with substantial societal and economic burdens. TAR in motor vehicle crashes is caused by a complex state of deformation progressing at high strain rates. A major step to gain insight into the possible mechanisms of TAR is to understand the mechanical behaviour of aortic tissue under loading conditions that leads to injury and failure. This study reports a total of 29 uniaxial tensile tests performed on porcine aortic tissue in the longitudinal and circumferential direction of loading. Uniaxial tensile tests were performed at targetted strain rates of 0.01/s, 70/s, 150/s and 250/s to failure. Engineering stresses reported in the study is calculated from the ratio of interially compensated measured force and initial cross sectional area whereas true strain is calculated by tracking the markers on the specimen surface using Matlab tm based digital image correlation (DIC) tool. The load – deformation behaviour of porcine aorta is found to be Non-Hookean and strain rate dependent with higher stiffness in circumferential direction compared to the longitudinal direction indicating the anisotropic behaviour of the tissue. As strain rate increased to 250/s, the failure stress ranged from 1.64 MPa to 4.84 MPa and 1.98 MPa to 7.05 MPa for longitudinal and circumferential tissues respectively. For the same range of strain rate, failure strain ranged from 26% to 37% and 24% to 42% and the elastic modulus changed from 9.42 MPa to 31 MPa and 12.33 MPa to 51 MPa for longitudinal and circumferential tissues respectively.